Employee Performance Assessment System of PT. Graha Prima Mentari Medan by Using Simple Additive Weighting - Cristian, Niel; Mansyur, Abil (ZERO: Jurnal Sains, Matematika dan Terapan, 2021)
Employee performance appraisal system is a system used to assess the best performance of employees. PT Graha Prima Medan performs the best performance assessment of employees to evaluate, verify and improve their performance. The results of this performance become a decision-making tool such as promotion, dismissal, transfer, intensive giving or providing feedback for employees. However, the large number of employees who will be selected becomes an obstacle in assessing employee performance, because it is expected that an automation process uses technology to evaluate the performance of these employees. The purpose of this study is to design an employee performance appraisal system at PT Graha Prima Mentari Medan. The method used is the SAW method, the basic concept of the SAW method is to find the weighted sum of the performance ratings for each alternative on all attributes. The SAW method can help decision making to form the largest value as the best alternative. The assessment in the research that has been carried out uses 5 criteria including: Attendance, Attitude, Time Discipline, Working Period and Quantity using the SAW method. In this study, testing was carried out on 36 respondent data. The employee performance appraisal system was developed using the PHP (Pre-Hypertext Processor) programming language, and the MySQL database as the database server.